Perawatan Kulit Topical Probiotics Pada Lansia di Panti Tresna Werdha Budi Mulia 2 Jelambar - Ulfah Nuraini Karim; Aliana Dewi; Erika Lubis (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2026)
Probiotics, prebiotics, and postbiotics have emerged as potential modulators of skin aging, with probiotics in particular being able to modulate the gut and skin axis, reduce inflammation, and promote skin rejuvenation. The purpose of this community service is to provide Topical Probiotics Skin Care for the Elderly at the Budi Mulia 2 Jelambar Nursing Home. In implementing this community service activity, the author conducted a Professional Guidance Practice program with the aim of providing nursing care and learning in community service carried out outside the campus. The methods used were Topical Probiotics Skin Care and health education and Demonstration. The results of this service showed that a significant change in the diagnosis of skin diseases with the provision of Topical Probiotics Skin Care for the elderly, namely the diagnosis of C2 to C1 and C1 to H1, changes in Elderly Knowledge were measured at the highest Pre Test 72 and Post Test 78, so there was an increase of 6 points. From the results of the activity, it is recommended to nurses to be more continuous in implementing Topical Probiotics Skin Care activities for the elderly and continuous monitoring and evaluation.